The personal archive of Manuel Villegas López: film texts for Unión Radio (1932-1936) - Diez Puertas, Emeterio (Documentación de las Ciencias de la Información, 2023)
This article presents the recording and cataloguing of a personal documentary collection dating from 1928 to 1936. It is part of the archive formed from the legacy of the film critic Manuel Villegas López (1906-1980). It consists of around 750 documentary units. In particular, this collection is rich in radio scripts, as it belongs to Villegas’ activity at the Unión Radio station (1925-1939). The research has made it possible to classify nearly 200 texts by title, date and program, 70% of them unpublished for us.